Identifikasi Gen 16S rRNA Bakteri Asam Laktat UBC-DTK-01 dari Dadih - Azizah Azizah; Minda Azhar (Departemen Kimia FMIPA UNP, 2022)
Genotypic identification of bacteria is faster than phenotypic identification. This study aims to determine the group of lactic acid bacteria species from Tilatang Kamang Agam curd using the 16S rRNA gene. Bacterial chromosomal DNA was isolated using the kit wizard genomic DNA purification method. The 16S rRNA gene in chromosomal DNA was isolated by PCR method using BacF1 and UniB1 primers. The 16S rRNA gene fragment sequencing was carried out using the Dideoxy Sanger method. The sequenced nucleotide base sequences were analyzed using the BioEdit, BLASTn and MEGA X programs. The size of the 16S rRNA gene fragment of the bacterial isolate UBC-DTK-01 obtained was 1017 bp (base pair). The bacterial isolates belonged to the Enterococcus genus and Enterococcus faecalis species strain UBC-DTK-01.